(4+7)(5y+7)=0

Simple and best practice solution for (4+7)(5y+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+7)(5y+7)=0 equation:


Simplifying
(4 + 7)(5y + 7) = 0

Combine like terms: 4 + 7 = 11
(11)(5y + 7) = 0

Reorder the terms:
11(7 + 5y) = 0
(7 * 11 + 5y * 11) = 0
(77 + 55y) = 0

Solving
77 + 55y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-77' to each side of the equation.
77 + -77 + 55y = 0 + -77

Combine like terms: 77 + -77 = 0
0 + 55y = 0 + -77
55y = 0 + -77

Combine like terms: 0 + -77 = -77
55y = -77

Divide each side by '55'.
y = -1.4

Simplifying
y = -1.4

See similar equations:

| 6(3+8x)=-318 | | -2(5x-6)-(3x+3)= | | 8(.06m+21.80+.20(21.80))=241.92 | | -13c-35=9-2e | | 8x+7=6x+35 | | 2(4g-3)-8=4+2x | | 3x+27=195 | | -6(3w+5)+3w+5=w-45 | | 1(21)-2=19 | | n-(-12)=23 | | 10x+9-11-X=-4x-8-6x-6 | | 7p^2=17p-6 | | 65x+74=2089 | | (6x-1)-(10x-15)=0 | | 15=1+16t-4t^2 | | x+2x-3=5 | | 8(z+2)-4(3z+1)= | | 9(2n-2)=(4n+2)+1 | | 3x+6=393 | | 36.71=11.11+3.4t | | 27x^2+9y^2=0 | | 20x=10y+8 | | 2y-86=22x | | -2y-7-4y+8= | | 8x^2+8x=22 | | .5(2x-6)=6 | | 3b-5=8(6+5b) | | 3(4x-12)=48 | | 0=1+16t-4t^2 | | 9x=122 | | 0=1+16t+4t^2 | | (3x^2-3x+28)+(3x^2+6x-70)= |

Equations solver categories